EVALUATING VISUAL ELEMENTS IN TWO EFL TEXTBOOKS - Roohani, Ali; Sharifi, Mohammad (Universitas Pendidikan Indonesia, 2015)
Abstract: This study evaluates visual elements in two English textbooks, that is, Interchange 3 and Top Notch 3B, commonly taught to Iranian EFL learners; it analyzes illustrations to find out the balance of black-and-white and color drawings and photos and examines the extent to which visual materials are used for decorative purposes. The analysis of visual elements reveals that, first, color pictures constitute a large percentage of illustrations in both textbooks, reflecting current publication trend for stylish color pages. Second, Interchange 3 has more drawings than the Top Notch 3 whereas the Top Notch textbook has more photos, which can establish more authenticity and result in its higher price. Third, the majority of the portraits are color photos, and, further, actions are represented more through drawings than photos, presumably because of practicality issues. Finally, pictures used for decorative purposes constitute a small percentage of illustrations in both textbooks, indicating their pedagogically facilitative effects.Â